2018
DOI: 10.4172/1522-4821.1000404
|View full text |Cite
|
Sign up to set email alerts
|

Re-experiencing 9/11-Related PTSD Symptoms Following Exposure to Hurricane Sandy

Abstract: Background: Understanding Pre-Existing Posttraumatic Stress Disorder (PTSD) symptoms and risk of PTSD following Hurricane Sandy (Sandy) has important implications for PTSD screening of persons exposed to multiple traumas. This study assessed the association between Sandy exposure and a subset of PTSD symptoms related to re-experiencing trauma from the events of the September 11, 2001 (9/11). Methods: We studied 4,220 respondents from a random 8,870 person sample of adult World Trade Center Health Registry en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 19 publications
(31 reference statements)
0
10
0
Order By: Relevance
“…Our findings are more aligned to the protective-stabilizing model of resilience ( Fergus and Zimmerman, 2005 ) which suggested that prior lifetime trauma exposures as a protective factor helped neutralize the effect of additional trauma exposure. Another study ( Li et al, 2018 ) found additional trauma was not associated with increased risk of re-experiencing the prior traumatic event. Our current study thus adds new evidence that PTSD is associated with binge drinking change among those without prior trauma-related PTSD.…”
Section: Discussionmentioning
confidence: 98%
“…Our findings are more aligned to the protective-stabilizing model of resilience ( Fergus and Zimmerman, 2005 ) which suggested that prior lifetime trauma exposures as a protective factor helped neutralize the effect of additional trauma exposure. Another study ( Li et al, 2018 ) found additional trauma was not associated with increased risk of re-experiencing the prior traumatic event. Our current study thus adds new evidence that PTSD is associated with binge drinking change among those without prior trauma-related PTSD.…”
Section: Discussionmentioning
confidence: 98%
“…25,31,35,84,90,96,112,127 • In mental health support interventions, screen for previous disaster exposures and other past traumas to identify populations at risk. 37,41,87,98,102,106 • In counselling protocols, account for history of post-traumatic stress disorder symptoms from past disasters. 94 • Whereas post-traumatic stress disorder and depression are commonly considered in public health screenings after a disaster, alcohol misuse, panic disorder, obsessive compulsive disorder and suicide risk are also relevant to screen for.…”
Section: Discussionmentioning
confidence: 99%
“…This occurrence was highlighted by studies that looked at populations exposed to both the 9/11 terrorism attacks and Hurricane Sandy in New York. 89,92,94,100,102,106 Other articles on mental health included a group of studies that focused on the identification of sociodemographic characteristics associated with increased risk of adverse mental health outcomes following multiple disasters (eg, by age, 48,51 gender, educational attainment, financial hardship, 35,57 and temporary housing experiences 111 ), with mixed results. Another group of articles focused on mental health risks faced by disaster responders 86,103,104 and public health workers 62,64 in the face of multiple disasters.…”
Section: Direct Implications For Public Health Mental Healthmentioning
confidence: 99%
“…Some survivors also witnessed traumatic events such as seeing airplanes strike the towers. These exposures led to the development of a variety of physical and mental conditions, such as asthma [ 1 , 2 , 3 , 4 , 5 ], post-traumatic stress disorder (PTSD) [ 6 , 7 , 8 , 9 ], heart disease [ 6 , 10 , 11 ], stroke [ 8 ], and cancer [ 12 , 13 ]. Some of these diseases appeared in survivors in the first several years after the attacks (e.g., asthma, PTSD), while other diseases have longer latency periods and have appeared 10–15 years after the 9/11 attacks (e.g., heart disease, stroke, certain cancers).…”
Section: Introductionmentioning
confidence: 99%